Seasonal and diurnal variation of lightning activity over southern Africa and correlation with European whistler observations - (:unkn) unknown (My University, 2006)
Lightning Imaging Sensor (LIS) data have been analysed to ascertain the statistical pattern of lightning occurrence over southern Africa. The diurnal and seasonal variations are mapped in detail. The highest flash rates (107.2 km-2 y-1) occur close to the equator but maxima are also found over Madagascar (32.1 km-2 y-1) and South Africa (26.4 km-2 y-1). A feature of the statistics is a relatively steady contribution from over the ocean off the east coast of South Africa that appears to be associated with the Agulhas current. Lightning statistics are of intrinsic meteorological interest but they also relate to the occurrence of whistlers in the conjugate region. Whistler observations are made at Tihany, Hungary. Statistics reveal that the period of most frequent whistler occurrence does not correspond to the maximum in lightning activity in the conjugate region but is strongly influenced by ionospheric illumination and other factors. The whistler/flash ratio, R, shows remarkable variations during the year and has a peak that is narrowly confined to February and March.
Keywords: African Research